Synthesis of aromatic cytokinins for plant biotechnology - Plíhalová, Lucie; Vylíčilová, Hana; Doležal, Karel; Zahajská, Lenka; Zatloukal, Marek; Strnad, Miroslav (New biotechnology, 2016)
Cytokinins represent an important group of plant growth regulators that can modulate several biotechnological processes owing to their ability to influence almost all stages of plant development and growth. In addition, the use of purine based cytokinins with aromatic substituent in C6 position of the purine moiety in tissue culture techniques is currently experiencing a surge in interest, made possible by the ongoing systematic synthesis and study of these compounds. This review article outlines progress in the synthesis of aromatic cytokinins, the in vitro and in vivo effects of these substances and insights gleaned from their synthesis. As the purine moiety in these compounds can be substituted at several positions, we examine each of the substitution possibilities in relation to the derivatives prepared so far. The discussion highlights the gradual simplification of their preparation in relation to their application in practice and summarizes the relevant organic chemistry literature and published patents.
Keywords: cytokininy; vývoj rostlin; Cytokinins; Molecular Structure; Plant Growth Regulators; regulátory růstu rostlin; puriny; molekulární struktura; biotechnologie; Purines; Biotechnology; Plant Development